2015
DOI: 10.3390/en9010009
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Validation of a Thermal Model of a Complex Roof Including Phase Change Materials

Abstract: This paper deals with the empirical validation of a building thermal model of a complex roof including a phase change material (PCM). A mathematical model dedicated to PCMs based on the heat apparent capacity method was implemented in a multi-zone building simulation code, the aim being to increase the understanding of the thermal behavior of the whole building with PCM technologies. In order to empirically validate the model, the methodology is based both on numerical and experimental studies. A parametric se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A phase change material (PCM) is one of the techniques that reduce energy demand in buildings .it can release and absorb huge amounts of energy through phase transitions with slight temperature changes. A lot of researches studied the effect of integrated of PCM with roof of the building on reducing energy consumption and improving thermal comfort [25] Figure 4 Operating Principle of BioPCM source: phasechangeenergy.com…”
Section: Figure 2 the Thermal Prosperities Of Cool Materials Source: ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A phase change material (PCM) is one of the techniques that reduce energy demand in buildings .it can release and absorb huge amounts of energy through phase transitions with slight temperature changes. A lot of researches studied the effect of integrated of PCM with roof of the building on reducing energy consumption and improving thermal comfort [25] Figure 4 Operating Principle of BioPCM source: phasechangeenergy.com…”
Section: Figure 2 the Thermal Prosperities Of Cool Materials Source: ...mentioning
confidence: 99%
“…In another study it found that addition of PCM layer with 0.15 cm thick to roof reduce indoor temperature 1.7 c in summer [27]. Numerous studies have been carried out to evaluate reducing the energy consumption and thermal comfort improvement in buildings if application PCMs on roof [28][29][30][31].…”
Section: Figure 2 the Thermal Prosperities Of Cool Materials Source: ...mentioning
confidence: 99%
“…It is important to highlight that the indoor air temperature of the building with or without PCM is predicted with a relative maximal error of accuracy of ±0.5°C. For more details, the interested reader may refers to [2], [5], [6].…”
Section: B Pcm Model In Isolabmentioning
confidence: 99%